ESTUDIOS DE FISIOLOGIA VEGETAL I ACCION DE LA INSULINA SOBRE LA CELULA VEGETAL - PRADO VILLAGRAN, FRANCISCO (Universidad Puebla, PUEBLA, PUEBLA, MEX, 1941)
Insulin (Lilly), 20 units per cc, in doses of 3 drops, pure; and in water solns, of 1, 2 and 3 parts per thousand, markedly activated the germination of wheat and bean seeds An increase in the development of bacteria and yeasts from the "aguamiel" (liq
ANS INST BIOL
Keywords: ESTUDIOS, FISIOLOGIA, VEGETAL, ACCION, INSULINA, CELULA, VEGETAL; CIENCIAS MEDICAS; FARMACOLOGIA